Some subjects of load flow calculation in shipboard integrated power systems - Kang Jun; Fu Lijun; Ma Fan; Wang Gang; Ye Zhihao; Fan Xuexin (2011 International Conference on Electrical Machines and Systems, 2011)
Modern shipboard integrated power systems require efficient and fast load flow solution methods. Classical load flow methods can't be applied directly because of the typical characters such as high R/X ratios, mixed AC and DC regions and ungrounded connection types. This paper illustrates some subjects of load flow calculation for shipboard power systems. Factors affecting the convergence of load flow equations are analyzed in details, which provide the precondition for solving load flow equations. Improvements on load flow methods for ungrounded distribution power systems are proposed due to the lost of ground reference in shipboard power systems. Especially, integrated AC/DC systems load flow approaches including three-phase converter models are also presented. Numerical examples demonstrate the validity and effectiveness of the proposed method.